2002
DOI: 10.1124/dmd.30.12.1441
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal Protein Concentration Modifies the Apparent Inhibitory Potency of CYP3A Inhibitors

Abstract: ABSTRACT:The effect of microsomal protein concentration on the inhibitory potency of a series of CYP3A inhibitors was assessed in vitro using Microsomal binding of drug substrates and/or metabolic inhibitors is increasingly recognized as a potential source of artifact arising in the course of in vitro studies of drug metabolism. Nonspecific binding of substrate to microsomal protein can influence availability of the substrate to the metabolizing enzyme or enzymes in vitro, and thereby yield biased estimates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 14 publications
3
54
0
Order By: Relevance
“…The 4-fold increase in IC 50 with addition of 4% HSA indicates that a decrease in the unbound concentration of OMP due to albumin binding results in a reduction in the extent of inhibition. An analogous effect was reported by Tran et al (2002) in microsomes; the inhibitory capacity of ketoconazole and OH-itraconazole on 3-HDZ formation from DZ was reduced using heat-inactivated protein.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The 4-fold increase in IC 50 with addition of 4% HSA indicates that a decrease in the unbound concentration of OMP due to albumin binding results in a reduction in the extent of inhibition. An analogous effect was reported by Tran et al (2002) in microsomes; the inhibitory capacity of ketoconazole and OH-itraconazole on 3-HDZ formation from DZ was reduced using heat-inactivated protein.…”
Section: Discussionmentioning
confidence: 59%
“…To quantitatively predict inhibition of metabolism in vivo, the concentration of inhibitor in the in vitro incubation should relate to the concentration of inhibitor in the plasma. Differences may result from the extensive binding of the inhibitor to microsomes, as demonstrated by Tran et al (2002) and Margolis and Obach (2003). In addition, differences may occur as a consequence of accumulation of the inhibitor in the hepatocyte as a result of intracellular binding or active cell uptake.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the high selectivity of tandem mass spectrometry reduces the potential for the compound being tested as an inhibitor to interfere in the analysis. Previous work has shown that inhibition constants can be altered by increasing microsomal protein concentration, due to nonspecific binding of the inhibitor to the (Margolis and Obach, 2003) and specific binding to the enzyme depleting the inhibitor (Gibbs et al, 1999;Tran et al, 2002). The use of very low microsomal protein concentrations should obviate the need to measure the free fraction of inhibitor in the in vitro matrices used.…”
Section: Validated Assays For Human Cytochrome P450 Enzymesmentioning
confidence: 99%
“…It has now been well established in the scientific literature that nonspecific binding of compounds into microsomal phospholipids will confound the experimental estimation of CL int and IC 50 by decreasing the fraction of unbound drug (fu mic ) to metabolizing enzymes within the incubation (Kalvass et al, 2001;Margolis and Obach, 2003;Obach, 1997Obach, , 1999Tran et al, 2002). In such cases, estimates of CL int and IC 50 derived from microsomes are best deemed "apparent" (i.e., CL int, app and IC 50, app ) because they represent a mixture of kinetic determinants with both relevant (CL int and IC 50 ) and irrelevant (fu mic ) implications for drug design by eqs.…”
Section: Introductionmentioning
confidence: 99%